Density-Optimized Lookup Table with Piecewise Linear Interpolation for ESP32 ADC Precision Enhancement - Antonius Irianto Sukowati; Linza Mawadda Rahmah (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
The inherent non-linearity of built-in Analog-to-Digital Converters (ADCs) in low-cost microcontrollers like the ESP32 significantly impacts measurement accuracy, often exceeding 10% error in critical ranges. This research aims to enhance ESP32 ADC precision without expensive external hardware through a novel software-based correction method. The proposed approach combines a density-optimized Lookup Table (LUT) with piecewise linear interpolation. Unlike conventional uniform distribution, this technique strategically concentrates 65% of calibration points in the critical mid-voltage region (0.5–2.5 V) where non-linearity is most pronounced. Experimental validation was conducted using precise input voltages from 0 V to 3.2 V across multiple ESP32 units. Results demonstrate remarkable improvements: the average absolute error was reduced from 0.112 V (3.42% of full scale) to 0.008 V (0.24% of full scale), with Root Mean Square Error (RMSE) decreasing by over 92.5%. The method achieves a sub-1% maximum error while maintaining minimal resource consumption, requiring only 264 bytes of memory and 2.3 ms processing time per measurement. These findings confirm that high-accuracy measurements are achievable using commodity hardware, challenging the notion that precision requires expensive external ADCs. This work offers significant implications for cost-sensitive IoT, environmental monitoring, and healthcare applications requiring reliable data acquisition without increased hardware complexity.